A Multicenter Study of donor deferral Rates and Reasons in Plateletpheresis (Northern International Medical College Journal, 2025)
Background: Demand for platelets has increased in recent years due to rising oncology cases, dengue fever, and other conditions associated with low platelet counts. The Transfusion Medicine Department plays a vital role in supplying apheresis platelet units with higher yields and fewer complications. Single donor platelet (SDP) units are particularly effective in raising platelet levels for patients and are processed through a device that separates platelets while returning the remaining components to circulation. Aim: To determine the donor deferral rates and reasons of deferred donors during plateletpheresis. Materials and Methods: This study was conducted in the Transfusion Medicine Department of BIRDEM, Apollo Hospital (Dhaka), and Asgar Ali Hospital in Dhaka from January 2021 to December 2021. Apheresis donors of either sex attending the mentioned departments were selected and deferred by physicians according to the Standard Operating Procedures (SOP) protocol followed by previously mentioned hospitals. The data of deferred plateletpheresis donors were recorded in a register and analyzed retrospectively. Results: Out of 1,191 plateletpheresis donors, 1,043 were chosen for single donor platelet (SDP) donation, while 148 (12.4%) were deferred for various reasons. The most frequent age group among the deferred donors was 26–35 years (53.3%). Among the deferred individuals, 67.5% were male and 32.4% were female. Most donors were temporarily deferred, making up 93.9%, while permanently deferred donors were 6.1%. The main reasons for temporary deferral included poor venous access (27.7%, primarily among females), low platelet count (16.2%), and drug use (most commonly analgesics) at 11.4%, with the least common cause being a non-matching blood group (2.1%). The most common reason for permanent deferral was seropositivity for HBsAg. Conclusion: Based on the findings of our study most of the deferred donors were between 26-35 years of age and male. The major causes of temporary donor deferral were poor venous access, low platelet count, drug use specially analgesics and underweight and the most common cause of permanent deferral was seropositivity for Hepatitis B.Northern International Medical College Journal Vol. 14 No. 1-2 July 2022-January 2023, Page 624-627